Anaerobic digestion of coffee waste - Neves, L. (2005)
The anaerobic co-digestion of five different by-products from instant coffee substitutes production was studied in mesophilic conditions. The co-substrate was the excess of sewage sludge from the wastewater treatment plant located in the same coffee factory. Four of the tested wastes produced methane in the range of 0.24-0.28 m³CH4(STP)/kgVSinitial . Reduction of 50-73% in total solids and 75-80% in volatile solids were obtained and the hydrolysis rate constants were in the range of 0.035-0.063 dֿ¹. After 40 days, one waste, composed of 100% barley, achieved a methane yield as low as 0.02 m³CH4(STP)/kgVSinitial and 31% and 40% total and volatile solids reduction, respectively,. Two different strategies were applied to enhance the biodegradability of this waste. An alkaline hydrolysis pre-treatment, that increased the methane production up to 0,22 m³CH4(STP)/kgVSinitial and the total and volatile solids reductions up to 67 and 84%, respectively. A co-digestion with kitchen waste, that increased the methane production up to 0,36 m³CH4(STP)/kgVSinitial and the total and volatile solids reductions up to 61 and 67%, respectively.